Virtual Reality Game Education to Learn Traffic Regulation - Andru Deva Lukito; Ridwan Sanjaya; Hendra Prasetya (SISFORMA, 2017)
Abstract – Traffic accident has become number 3 of children death cause in the world according to WHO[1]. Traffic accident that involve children often caused by their own by breaking the law or regulation. Therefor education about traffic regulation and law including traffic sign and its meaning must be given to children early. Because education means process to change a person or a group attitude and behavior in order to make them mature through teaching and training [2]. One of them that can be used is digital media.  One of interactive digital media is digital game, various form of digital game start from 2D, 2.5D, 3D with many point of view and new technology. VR (Virtual Reality) as new digital media where alternate reality exist to test various theory without any real consequences, according to Greenbaum “Virtual Reality is an alternate world filled with computer-generated images that respond to human movements. These simulated environments are usually visited with the aid of an expensive data suit which features stereophonic video goggles and fiber-optic data gloves”[3]. Greenbaum statement before were make VR suitable to test traffic law and regulation and educate kid to obey the traffic sign and regulation without real consequences from real world. This Journal contain the result of using virtual reality as traffic regulation education media. Education material that arranged consisting traffic sign that appear on the road and safety riding gear. Keywords – Virtual Reality, Traffic sign, Road traffic, children, education